Аналітичний огляд досліджень та розробок елементів систем підресорювання бронемашин легкої категорії за масою (оглядова стаття) - Зінченко, Олена Іванівна (Національний технічний університет "Харківський політехнічний інститут", 2021)
Проведений аналіз матеріалів з питань проєктування бронемашин легкої категорії. Розглянуті основні математичні моделі з моделювання динамічних процесів, напружено-деформованого стану у системі "бойовий модуль – корпус – підвіска". Проаналізовані публікації по проєктуванню торсіонних валів підвіски. Оскільки на сьогоднішній день відсутня відповідна теоретична база для розв'язання задач параметричного синтезу елементів систем підресорювання, а існуючі математичні моделі потребують вдосконалення, то ставляться основні задачі, які потребують розв'язання або вдосконалення існуючих рішень. Також потрібні такі розробки, які б враховували технічні рішення, процеси і стани, етапи виготовлення, умови експлуатації та бойового застосування, тобто такі, що відображали б усі етапи життєвого циклу елементів систем підресорювання легких броньованих машин.

The analysis of materials on the design of light armored vehicles is carried out. The main mathematical models for modeling dynamic processes, stress-strain state in the system "combat module - hull - suspension" are considered. The publications on the design of suspension torsion bars are analyzed. To date, the analysis and synthesis are not united by a single generalized parametrical description, which would cover both technical solutions of elements of suspension of light armored vehicles, modes of motion of these machines, and properties of materials of the elements under study, and requirements for tactics and technical characteristics in general. That is, there is no corresponding theoretical base for solving the problems of parametric synthesis of elements of suspension systems, and existing mathematical models need to be improved. Therefore, the main tasks that need to be solved or improved by existing solutions are set. Also, such developments are needed that would take into account technical solutions, processes and conditions, stages of manufacture, operating conditions and combat use, that is, those that would reflect all stages of the life cycle of the elements of suspension systems for light armored vehicles.
Analytical review of research and development of elements of suspension systems of armored vehicles of light category by mass (review article)
Keywords: легка броньована машина; тактико-технічні характеристики; торсіонний вал; системи підресорювання; підресорювана частина; підвіска; напружено-деформований стан; light armored vehicle; tactical and technical characteristics; torsion bar; suspension systems; sprung part; suspension; stress-strain state